Synthetic strategies and diversification of dibenzo[1,5]diazocines - Abdul, Qaiyum Ramle; Tiekink, Edward R. T. * (Royal Society of Chemistry, 2023)
Dibenzo[1,5]diazocine scaffolds are present in a wide range of organic building blocks, for example in pharmaceuticals, materials and structural chemistry. However, the development of these structural frameworks has not received significant attention owing to limited synthetic protocols and strategies. Herein, a summary of the attractive synthetic approaches for the construction of dibenzo[1,5]diazocines, epiminodibenzo[1,5]diazocines and epoxydibenzo[1,5]diazocines developed over the past two decades is presented. The spectroscopic, synthetic mechanisms for the formation of the heterocyclic rings and remarkable structural features, including in the solid-state, are discussed.